Educational Act, Regulations, and Their Key Issues in Nepal - Devkota, Krishna Maya; Tamrakar, Pratima; K.C., Rajendra (Educational Journal, 2026)
Education Act 1971 (2028 B.S.) is an innovative legal framework, which organized and improved the educational system. However, with the enactment of Education Regulation 2059 (2002 A.D.), provisions of Act 1971 along with its amendments have been implemented in Nepal. Therefore, this study has aimed to critically analyze the effectiveness and challenges of Education Act (1971) along with its implemented regulation (Education Regulation 2002) in Nepalese context. The purpose is to analyze the implementations and provide recommendations to enhance education. The method applied was qualitative and content-analysis approach which will analyze the legal texts, amendment provisions, and research documents. From the study findings, it is proved that both the systems have succeeded in providing a structure formal education and in raising the education access. However, issues of over-centralization of decision-making powers, limitation in policy implementation authorities, low resource, political interference to teachers and inequity access and quality have remained the central problems. The study has strongly concluded that there is urgent need for major reform to these laws so that it becomes more federal-friendlier, inclusive and addresses present issues by incorporating up to date techniques such as e-learning, vocational and technical education. An implication from this study would be that, effective decentralization along with strong local capacity and accountability mechanism is essential for ensuring equity, efficiency and quality education for Nepal.